DEMOKRASI DAN POLITIK PENCITRAAN PERANG IKLAN POLITIK MENUJU DEMOKRATISASI DI INDONESIA - Grendi Hendrastomo * (Dimensia: Jurnal Kajian Sosiologi, 2009)
Democracy has become one of the best governmental systems adopted by countries all over the world. Democracy has considered able to respond more intentions particularly public’s in fighting for people’s right. There must be at least under these three conditions for a country to be considered as democratic country. First, it must run general election, empowered civilians and freedom of the press. General election is one way a citizen can contribute in politic. General election is held every five years and is used as a media to distribute their voices by voting the representative who will become the spokeperson in the parliament. To be a representative is not an easy job. Resources (social resources) are needed to win the popular vote. This is then why the representative democracy requires imaging. It is a common knowledge that the candidate of representative does not necessarily know the people he represent. Democracy raises the euphoria of creating image. In the end, war of image-making where character, quality, and individual’s quality can be imaged and sell to public will happen. Political commercial’s war has spreaded which force people to enjoy. Democracy then is identical with politic of imaging. Voters then are similar as the decision makers of the economy. Political party or individual is voted based on its marketing, no different with the marketing of groceries. Economic capital has become political basis to someone hence finally creating the democratical chain which costs a big amount. Eventhoungh in one side, the politic of imaging lowers the quality of democracy; on the other hand, it gives political study to people so the public will gain more politic knowledge from the politic ads. Key words: democracy, politic, imaging